ANALISIS PENGUKURAN KINERJA KEUANGAN BERDASARKAN RASIO PROFITABILITAS PADA PT. ASTRA AGRO LESTARI, TBK - SUMISUSILAWATI, SUMISUSILAWATI; NURHAYATI, NURHAYATI (GANEC SWARA, 2024)
This study is to determine the financial performance of PT Astra Agro Lestari, Tbk in terms of profitability ratios for the period 2013-2022. The type of research used in this research is descriptive quantitative. This research was conducted to determine and analyze the profitability ratio to assess the financial performance of PT Astra Agro Lestari, Tbk. In measuring the company's financial performance. The data analysis technique used is the profitability ratio which includes Net Profit Margin (NPM), Return On Asset (ROA), Return On Equity (ROE). By using the one sample T-test test with the help of SPSS Version 22. The sample used is purposive sampling with certain sampling with available data for the last 10 years, namely from 2013-2022. The results of the analysis show that the financial performance of Net Profit Margin (NPM) the company's financial performance is in the very good category because it is above the average standard of the company's industry and for Return On Asset (ROA) and Return On Equity (ROE) the company's financial performance is in the poor category because it is below the average standard of the company's industry